Extended State Observer based control for coaxial-rotor UAV. (March 2016) - Rida Mokhtari, M.; Choukchou Braham, Amal; Cherki, Brahim
Abstract: This paper considers the problem of controlling the position and the orientation of a Coaxial-Rotor Unmanned Aerial Vehicle -CRUAV- despite unknown aerodynamic efforts. A hierarchical flight controller is designed, allowing the trajectory tracking and the stabilization of the vehicle. The designed controller is build through a hierarchical approach yielding two control loops, an inner one to control the attitude and an outer one to control the translational trajectory of the rotorcraft. An Extended State Observer -ESO- is used to estimate the state and the unknown aerodynamic disturbances. The analysis further extends to the design of a control law that takes the disturbance estimation procedure into account. Numerical simulations are carried out to demonstrate the efficiency of the proposed control strategy.